Physicochemical, textural, and antioxidant properties of Pandan Leaf Extract (PLE)-fortified gummy jelly - Booranasakawee, Natnirin; Siricoon, Sinee; Donrung, Nowwapan; Ploypetchara, Thongkorn (Journal of Applied Research on Science and Technology (JARST), 2025)
The presented study focuses on fortifying pandan leaf extract (PLE) into a gummy product. The PLE preparation using two carrier agents, Tween 80 (P3) and black sesame oil (P4), was applied before adding to gummy processing. Then, the PLE-fortified gummy optimization was conducted by varying the PLE concentration at 1.0% (F1), 1.5% (F2), and 2.0% (F3) by weight. Their physicochemical properties were measured by textural by Texture Profile Analysis (TPA), and In-vitro biochemical properties of PLE-fortified gummy were analyzed. Results of the first experiment showed that there are significant differences in pH value, total soluble solids, and color attributes, with the black sesame oil-based formulation exhibiting higher lightness (L* value) and yellowness (b* value) values (p <0.05). The result of the TPA analysis showed that the PLE-fortified gummy with black sesame oil formulation had higher hardness and chewiness than the PLE-fortified gummy with Tween 80 formulation (p <0.05). For the second experiment, the physicochemical results demonstrated that total soluble solids, acidity, and color values increased when PLE-extract concentration was added (p<0.05). Regarding increasing PLE-extract levels, the texture of gummy jelly showed a decrease in hardness and gumminess while springiness increased (p <0.05). Antioxidant properties, including free radical scavenging activity by DPPH and ABTS assays, supported the potential health benefits of pandan leaf extract in gummy jelly. This study suggests that black sesame oil is a suitable carrier for preparing pandan leaf extract for gummy production. Therefore, the PLE-fortified gummy can be produced as a functional confectionery product, paving the way for future applications in health-oriented gummy formulations.